Keterbatasan Kekuatan Eksekutorial Putusan Pailit Indonesia dalam Perkara Kepailitan Lintas Negara - Elirica Aliyah Irwan Bauw; Ema Nurkhaerani (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This study examines the issue of cross-border insolvency in the context of Indonesian bankruptcy law, particularly the limitations of national law in handling cases involving foreign elements such as assets or creditors outside Indonesia. Although Law Number 37 of 2004 contains universal principles, its implementation is hindered by Indonesia's adherence to the principle of territoriality and the absence of international agreements on mutual recognition and enforcement of foreign bankruptcy decisions. This normative legal research employs statutory and conceptual approaches to analyze the legal framework and principles relevant to cross-border insolvency. The findings show that Indonesian bankruptcy rulings currently have limited extraterritorial effect and cannot be directly enforced abroad without proper international legal instruments. To overcome these limitations, the adoption of the UNCITRAL Model Law on Cross-Border Insolvency is deemed necessary, along with efforts to establish bilateral or multilateral agreements. Such steps are expected to enhance legal certainty, protect creditors’ rights, and improve Indonesia’s insolvency regime in the context of global commerce.